Pentingnya Kesadaran Pajak dan Analisis Sistem Informasi Akuntansi Penjualan pada Toko Dumai Terpal - Edy Prabowo; Rorisky Nababan; Vivien Angelin; Nurpita Reni Sianturi; Nindy Rachmadiny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to explore the importance of tax awareness and the analysis of sales accounting information systems at Toko Dumai Terpal, a micro, small and medium enterprise in Dumai City. This study seeks to understand the factors influence the level of tax compliance among UMKM and the role of sales accounting systems in supporting transparency and efficiency. The research method employed includes direct interviews, documentation, and literature review, with primary data sourced from the business owner and secondary data from the company's financial archives. The research results show that the lack of tax awareness among UMKM taxpayers has a negative impact on tax compliance. The sales system which is currently manual based with Microsoft Excel support is deemed less than optimal in managing sales transactions and accurate reporting. The results show that the Dumai Tarpaulin Store experienced an increase in sales of 32.90% from 2021 to 2022. This increase was influenced by meeting customer needs for appropriate tarpaulin product variants, competitive prices, as well as improving economic conditions after the COVID-19 pandemic. The conclusion of this study highlights that increasing tax awareness and implementing a more structured accounting system can drive operational efficiency, improve tax compliance, and support sustainable business growth.